Demographic Gaps Between Syrian and the European Populations: What do they suggest? - Yucesahin, Mustafa Murat; Sirkeci, Ibrahim (Border Crossing, 2017)
Syrian crisis resulted in at least 6.1 million externally displaced people 983,876 of whom are in Europe while the rest are in neighbouring countries in the region. Turkey, due to its geographical proximity and substantial land borders with the country, has been the most popular destination for those fleeing Syria since April 2011. Especially after 2012, a sharp increase in the number of Syrian refugees arriving in Turkey was witnessed. This has triggered an exponential growth in academic and public interest in Syrian population. Numerous reports mostly based on non-representative sample surveys have been disseminated whilst authoritative robust analyses remained absent. This study aims to fill this gap by offering a comprehensive demographic analysis of the Syrian population. We focus on the demographic differences (from 1950s to 2015) and demographic trends (from 2015 to 2100) in medium to long term, based on data from World Population Prospects (WPP). We offer a comparative picture to underline potential changes and convergences between populations in Syria, Turkey, Germany, and the United Kingdom. We frame our discussion here with reference to the demographic transition theory to help understanding the implications for movers and non-movers in receiving countries in the near future.